Heterostructural nanoadjuvant CuSe/CoSe₂ for potentiating ferroptosis and photoimmunotherapy through intratumoral blocked lactate efflux - Yang, Chunzheng (2023)
The desirable curative effect in clinical immunotherapy has been challenging due to the immunosuppressive tumor microenvironment (TME) with high lactic acid (LA) metabolism in solid tumors. Although targeting metabolic reprogramming of tumor cells can restore the survival and function of immune cells in the TME, it is also plagued by insufficient immunogenicity. Herein, an activatable immunomodulatory nanoadjuvant CuSe/CoSe2@syrosingopine (CSC@Syro) is constructed for simultaneously relieving immunosuppressive TME and boosting tumor immune response. Specifically, CuSe/CoSe2 (CSC) exhibits TME-activated glutathione (GSH) depletion and hydroxyl radical (•OH) generation for potential ferroptosis. Meanwhile, the remarkable photothermal conversion efficiency and elevated photocatalytic ROS level both promote CSC heterostructures to induce robust immunogenic cell death (ICD). Besides, the loaded syrosingopine inhibitor achieves LA metabolism blockade in cancer cells by downregulating the expression of monocarboxylate transporter 4 (MCT4), which could sensitize ferroptosis by intracellular milieu acidification and neutralize the acidic TME to alleviate immunosuppression. Hence, advanced metabolic modulation confers the potentiated immune infiltration of ICD-stimulated T lymphocytes and further reinforces antitumor therapy. In brief, CSC@Syro-mediated synergistic therapy could elicit potent immunogenicity and suppress tumor proliferation and metastasis effectually by integrating the tumor metabolic regulation and ferroptosis with immunotherapy.